Brozopine ameliorates cognitive impairment via upregulating Nrf2, antioxidation and anti-inflammation activities - Fu, Zhenzhen; Wang, Xuening; Fan, Yanan; Shang, Dong; Zhang, Jiahua; Xiao, Tingting; Guo, Jiajun; Wang, Yi; Wang, Zhiyu; Zhang, Zixin; Jia, Qingran; Zhu, Jinpeng; et al. (Frontiers in Pharmacology, 2024)
Oxidative stress and inflammation are crucial factors contributing to the occurrence and development of vascular dementia (VD). In a previous study, we demonstrated that brozopine (BZP) is an anti-ischemic drug. In this study, a model of VD in rats with modified permanent bilateral common carotid artery occlusion (2-VO) was established in vivo, a model of cellular excitotoxicity/oxidative stress was established via L-glutamate-induced PC12 cell injury, a model of neuroinflammation was established in LPS-induced BV2 cells in vitro, and the ameliorative effect of BZP on cognitive impairment was assessed. BZP treatment improved memory deficit in VD rats through inhibiting Ca 2+ overload and the levels of oxidative stress, ferroptosis, and inflammatory markers (IL-1β, IL-6, and COX-2) in different brain regions. Additionally, we found that the levels of inflammatory markers in the plasma were also reduced in the VD rats. BZP was further found to have antioxidative stress, antiferroptosis (ferroptosis markers: GPX4, P53, and ACSL4), and antineuroinflammatory effects in PC12 and BV2 cells. Its mechanisms of action were found to be related to the activation of the Nrf2/TLR4/NF-κB pathway; the protective effect of BZP was partially inhibited after using Nrf2-specific inhibitors. Thus, BZP has therapeutic properties for the potential mitigation of cognitive impairment.